Analisis Pencatatan dan Penilaian Persediaan Sesuai PSAK Nomor 14 - Hakim, Lukmanul; Khotimah, Husnul; S, Salbiah (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The purpose of this research is to determine the recording and assessment of finished goods inventory carried out by PT Berangan Ragam Rasa. This research method is Descriptive Qualitative. Data collection techniques were carried out by means of documentation and interviews. The results of this research found that the inventory recording method uses the perpetual method in this case in accordance with expert theory. And the assessment system uses the FIFO method or the product produced first will be issued first. The assessment of finished goods inventory at PT Berangan Ragam Rasa has been carried out well and in accordance with the Statement of Financial Accounting Standards (PSAK) No. 14 concerning inventory. The suggestion that researchers can convey to PT Berangan Ragam Rasa is that the owner needs to be aware of recording each finished goods inventory so that there is no difference between the amount of finished goods inventory in the warehouse and that in the records and to make it easier to make decisions when knowing the inventory. thin so that delays in inventory will not occur.